Learners’ Identity Construction in the Context of English as an International Language - Guerra, Luis (2013)
According to Riley (2007) the term ‘identity’ can be used to talk about what makes individuals just that, individual, who self-reports using the pronoun ‘I’, which is subjective and private. On the other hand, we can also use ‘identity’ to talk about what makes this individual like other individuals in terms of shared characteristics and memberships, the ‘you’ that others address and construct, report on and to. These two spheres, the collective and individual identities, exist and impact on one another reciprocally. In these circumstances, the construction of self is a continuous process. This paper aims to explore connections between identity construction and language use within the context of English as an international language. More specifically, it focuses on the Portuguese learners' own perceptions of their language use and on their discursive construction of identities, identifying the negotiations implied in the process of collective and individual identities construction.